Effects of calcium channel blocker, nifedipine, on antidepressant activity of fluvoxamine, venlafaxine and tianeptine in mice - Sharma, Ashok K.; Khadka, Anjan; Dahiya, Navdeep (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Cardiovascular diseases are commonly associated with depression. Calcium channel blockers (CCBs) form commonly used group of drugs for the treatment of a number of cardiovascular diseases. Nifedipine, a CCB, has been shown to possess antidepressant activity and potentiate antidepressant activity of imipramine and sertraline, however, literature on its interaction with newer antidepressant drugs such as fluvoxamine, venlafaxine and tianeptine is limited. Hence, the present study was undertaken. Methods: The study was carried out in albino mice in two phases. In Phase I, antidepressant activity of nifedipine, fluvoxamine, venlafaxine and tianeptine were confirmed after their single dose administration using forced swim test (FST) and tail suspension test (TST) and their minimum antidepressant doses were determined. In Phase II, the effect of nifedipine on antidepressant activity of fluvoxamine, venlafaxine and tianeptine was studied by orally administering sub-antidepressant doses of these drugs for 28 days. FST and TST were carried out on 1st, 14th and 28th day of the study and change in immobility period was observed. Results: In Phase I, all the studied drugs exhibited dose dependent antidepressant activity in both FST and TST. Minimal antidepressant dose of nifedipine, fluvoxamine, venlafaxine and tianeptine was observed as 10, 25, 25 and 10 mg/kg respectively. In Phase II, combinations of sub-antidepressant dose of nifedipine (5 mg/kg) with sub-antidepressant doses of fluvoxamine (12.5 mg/kg), venlafaxine (12.5 mg/kg) and tianeptine (5 mg/kg) exhibited enhanced antidepressant activity when compared to the control group and individual drug groups after same duration of treatment. Conclusions: Nifedipine, fluvoxamine, venlafaxine and tianeptine possess antidepressant activity and nifedipine exhibits synergistic antidepressant activity with fluvoxamine, venlafaxine and tianeptine.